Case theory in business and management : - Gummesson, Evert (Sage Publications Ltd, 2017)
This book will appeal to students, academics and researchers who are interested in the science and philosophy behind case study research as well as the methodology and a thought-provoking read for anyone who wants to be challenged about their belief of case study theory.